Multiple athletic performances, maturation, and Functional Movement Screen total and individual scores across different age categories in young soccer players - Bakalár, I; Šimonek, J.; Kanásová, J.; Krcmárová, B.; Krcmár, M. (Journal of Exercise Rehabilitation, 2020)
The purpose of this study was to evaluate differences in multiple athletic performances, and to examine associations between athletic performance and Functional Movement Screen (FMS) in young soccer players. Forty-one soccer players were tested on peak height velocity (PHV), 5-, 10-, and 30-m sprint times, 505 change of direction (505 COD), Y-reactive agility tests, countermovement jump (CMJ), and squat jump (SJ) height. Significant main effects (P<0.01) were recorded in all tests except FMS total score whereas the U16 group outperformed U12 and U14 in almost each test. However, when the results were adjusted to the PHV 7 of 11 tests were nonsignificant. Significant associations were recorded between trunk stability push-up (TSPU) and 5 m (P=0.04) and 505 COD (preferred) times (P=0.01), and SJ height (P=0.03) in the U12. In the U14, significant associations were recoded between TSPU and SJ (P<0.01) and CMJ height (P=0.03). In the U16, significant associations were recorded between deep overhead squat and 5-m sprint time (P=0.02) and CMJ height (P=0.04). Results of this study indicate that athletic performance in young soccer players is multidimensional in nature, and it is a consequence of several factors including maturation, different training strategies, and movement proficiency.